PREVALENCE OF DIABETIC COMPLICATIONS IN NEWLY DIAGNOSED TYPE 2 DIABETES PATIENTS IN PAKISTAN: FINDINGS FROM NATIONAL REGISTRY - Uddin, Fareed; Ali, Beena; Junaid, Nabeea (Journal of Ayub Medical College Abbottabad, 2019)
Background: This study was conducted to assess the prevalence of micro- and macrovascular complications in patients with newly diagnosed type 2 diabetes (T2DM) in Pakistan. Methods: In this multicentre, observational, cross-sectional disease registry, patients (aged ‰¥18 years) who were diagnosed at enrolment with T2DM, defined by fasting blood glucose (FBG) ‰¥126 mg/dL and/or glycated haemoglobin (HbA1c) ‰¥6.5%, were enrolled. Microvascular complications were ascertained by objective examination while macrovascular complications were identified from patients’ medical history. Descriptive statistics were used for data analysis. Results: Data from 891 patients were analysed in the study. Mean [±standard deviation (SD)] HbA1c, FBG, and random blood glucose were 9.9% (±2.2%), 193.4 (±74.0) mg/dL, and 294.3 (±72.7) mg/dL, respectively. Obesity (n=689, 77.3%) and familial history of diabetes (n=575, 64.3%) were the most common risk factors for T2DM. Overall prevalence of micro- and macrovascular complications was 68.6% [n=611, 95% confidence interval (CI): 65.4-71.5] and 9.0% (n=80, 95% CI: 7.3-11.0), respectively. Neuropathy, nephropathy, and retinopathy were reported in 59.6% (95% CI: 56.3-62.8), 24.4% (95% CI: 21.6-27.2), and 15.9% (95% CI: 13.7-18.5) of the patients, respectively. Oral antidiabetic agents and insulin were prescribed to 839 (94.2%) and 140 (15.7%) patients, respectively. All study patients received education on T2DM management, mostly from the investigators, and also from diabetes educators and nurses. Conclusions: The prevalence of micro- and macrovascular complications of T2DM is high, indicating a delay in diagnosis of disease. In order to counter the burden of diabetic complications, optimum strategies for screening of the general population are required. Keywords: Type 2 diabetes mellitus; Complications; retinopathy; neuropathy; nephropathy; myocardial infarction; stroke; acute coronary syndrome; peripheral arterial disease; Pakistan